7 The impact of in-situ simulation training on individual and team performance during real cardiopulmonary resuscitations on a paediatric intensive care unit (picu). (17th November 2016) - MacGloin, H; Lofton, L; Sanz, D; Gruendler, K; Korb, C; Storey, L; Desai, A; Lane, M; Banya, W; Sampaio, H; De Costa, K; Burmester, M
Abstract : Outcome after cardiopulmonary resuscitation (CPR) is influenced by the resuscitation team response. 1–3 Our in-situ simulation training programme aims to improve patient outcome by rehearsing the team response to simulated crises including cardiac arrests. 4 There is a relative paucity of translational research on the impact of simulated team training on real resuscitations. 5 Aims: We aimed to assess the impact of simulation training on individual performance, team-working and Crisis Resource Management (CRM) during real cardiopulmonary resuscitations (CPR). Methods: Bi-monthly simulation sessions include advocacy-enquiry debriefing and CRM training. Cardiac arrests on PICU requiring at least 2 minutes of CPR were audited (1.5.2014 to 31.5.2015). Following each resuscitation, team members completed anonymous questionnaires scoring team resuscitation performance using the validated TeamMonitor tool 4 and the impact of prior simulation training on self-rated performance. Results: 234 resuscitation questionnaires from 36 cardiac arrests were analysed. Prior simulation training was highly significant particularly for improving individual overall CPR performance and assisting early calls for help for the resuscitation (p = 0.001). Prior simulation training improved staff self-rating of performance and confidence during the resuscitation with little variability and strong mean agreement across groups. Consistency of skills during CPR was reported for leadership and role shifting in response to emerging events during the resuscitation (75.92%, n = 180). 36 resuscitation team responses were analysed for consistency of CRM reported by at least 75% of members. Consistent leadership was reported by 21 teams (58.3%). Average team service length did not influence the proportion of teams reporting consistent CRM skills for most dimensions of team-working. Conclusions: During real CPR, self-evaluated performance improves significantly with prior simulation training; particularly attendance at more than 3 sessions. Further research is required to assess barriers to consistency of application of CRM during resuscitations and the impact of simulation team training on patient outcome. References: Peddy S, Hazinski MF, Laussen PC, et al . CPR: special considerations for infants and children with cardiac disease. Cardiol Young 2007;17 (Suppl 2):116–126. Abella BS, Alvarado JP, Myklebust H, et al . Quality of CPR during in-hospital cardiac arrest. JAMA 2005;293 :305–310. Hunt E, Patel S, Vera K, et al . Survey of paediatric resident experiences with resuscitation training and attendance at actual cardiopulmonary arrests. Pediatr Crit Care Med 2009;10 (1):96–105. Stocker M, Menadue L, Kakat S, et al . Reliability of team-based self-monitoring in critical events: a pilot study. BMC Emerg Med 2013:13 :22. McGaghie W, Issenberg SB, Barsuk JH, Wayne DB. A critical review of simulation-based mastering learning with translational outcomes. Med Ed 2014;48 :375–385.